Bit by byt towards a contemporary conjoint interior: from Dom Narkomfin to a new social condenser. (1st September 2016) - Stevens, Ruth; Petermans, Ann; Vanrie, Jan
Abstract: Conjoint interiors, the semi-public interior spaces located in, for example, large-scale dwelling projects, host different functions for a variety of users. Designers of conjoint interiors today face the major challenge of accommodating the increasingly varied design briefs of this variety of users. In these environments, people today tend to emphasize intangible qualities, the "feel" of the environment, much more than tangible ones, that is, the "look" of the environment. Consequently, instead of working with a purely spatial design brief, designers are now required to work with more emotional briefs, taking into account not only the objective and physical characteristics, but also more subjective requirements. Although it is clear that designers of these conjoint interiors will need to work within a more human-centered framework, the question remains of how this process can become more focused towards creating intangible qualities and specific spatial affordances. To address this question, our contribution investigates the intangible qualities and the design approach of two cases: Dom Narkomfin, the so-called "social condenser" (designed by Ginzburg in 1928), and Layer Cake, the outcome of a 2015 design exercise of a residence for older persons that approaches the conjoint interior from a renewed social perspective. These cases will be analyzed via two lenses: (1) a societal perspective, researching context and target group, and (2) a more anthropological perspective, focusing on experiences and intangible design qualities. The results will be used to propose architectural-theoretical principles that attempt to reinvigorate the "social condenser" concept as a way to address new design briefs in conjoint interiors today.